Relation of Visceral and Subcutaneous Adipose Tissue to Bone Mineral Density in Chinese Women. (3rd June 2013) - Wang, Ling; Wang, Wei; Xu, Li; Cheng, Xiaoguang; Ma, Yimin; Liu, Dan; Guo, Zhe; Su, Yongbin; Wang, Qianqian
Abstract : The relationship between adipose and bone tissues is still being debated. The purpose of our study was to evaluate whether the distribution and volume of abdomen adipose tissue are correlated to trabecular bone mineral density in the lumbar spine. In this cross-sectional study, 320 Chinese women, being divided into two groups according to age ≥55 years and <55 years, were evaluated with quantitative computed tomography (QCT) of the spine to simultaneously evaluate the average trabecular BMD of L2–L4, VAT, and SAT. Possible covariates of height, weight, age, and comorbidities were considered. In the <55-year-old sample, multiple linear regression analyses indicated that VAT volume was negatively correlated to trabecular BMD (P value = 0.0003) and SAT volume had no correlation to trabecular BMD. In contrast, there was no significant correlation between VAT or SAT and BMD in the ≥55-year-old sample. Our results indicate that high VAT volume is associated with low BMD in Chinese women aged <55 years and SAT has no relation with BMD.